Phytochemical Profile, and Antiproliferative and Proapoptotic Effects ofPouteria ramiflora(Mart.) Radlk. Leaf Extract, and Its Synergism with Cisplatin in HepG2 Cells - Tuttis, Katiuska; Costa, Daryne Lu Maldonado Gomes da [UNESP]; Serpeloni, Juliana Mara; Santos, Lourdes Campaner dos [UNESP]; Varanda, Eliana Aparecida [UNESP]; Vilegas, Wagner [UNESP]; Martinez-Lopez, Wilner; Colus, Ilce Mara de Syllos (Mary Ann Liebert, Inc, 2020)
Different species of the genusPouteriahave been used in folk medicine for the treatment of inflammation, fever, ulcers, diabetes, and diarrhea. We analyzed the phytochemical profile of the hydroethanolic extract fromPouteria ramifloraleaves by electrospray ionization ion trap tandem mass spectrometry and high-performance liquid chromatography-diode array detection, and examined whether it alone and in combination with cisplatin interfered with cell proliferation and death processes in HepG2 (human hepatocellular carcinoma) and FGH (human gingival fibroblasts) cells. Five compounds were identified in the extract: gallic acid, myricetin-3-O-alpha-l-arabinopyranoside, quercetin-3-O-beta-d-galactopyranoside, myricetin-3-O-alpha-l-rhamnopyranoside, and myricetin-3-O-beta-d-galactopyranoside. The extract was cytotoxic to both cell lines by inducing apoptotic cell death and acted in synergy with cisplatin; such effect was stronger in HepG2 cells than in FGH cells, demonstrating some selectivity to tumor cells. In HepG2 cells, the extract exerted antiproliferative effect mediated by induction of cell cycle arrest at the S and G2/M phases. Association of the extract with cisplatin enhanced the latter's antiproliferative effect, arrested the cell cycle at the S phase byCDK2modulation, and reduced the number of anti-cyclin D1-stained HepG2 cells. Simultaneous treatment with the extract and cisplatin increased the latter's cytotoxicity, apoptotic cell death, andBAXexpression in HepG2 cells. Altogether, the results reported herein indicate thatP. ramifloraextract is a possible adjuvant to cancer therapy, which can circumvent the cisplatin-mediated resistance mechanisms in cancer cells.
Keywords: antitumor; apoptosis; flow cytometry; immunocytochemistry; medicinal plant; RT-qPCR